THE PREVALENCE OF CHECK NDM-1 GENE CAUSING BETA- LACTAM ANTIBIOTIC RESISTANCE IN KLEBSIELLA PNEUMONIAE ISOLATES FROM CLINICAL SAMPLES AND PLASMID CURING: Pharmaceutical Science-Biotechnology - SHAEBANI; ALIAKBAR; GHANADIAN ABDOLHAMID; GHANADIAN MOHAMMAD ALI (International Journal of Life Science and Pharma Research, 2022)
Existence of extended spectrum B-lactamase (ESBL) genes plays an important role in causing B- lactam antibiotic resistance in the producing strains of these anzymes. The resistance of gram- negative bacteria, such as klebsiella pneumonia, to different antimicrobial agents, especially B- lactam and carbapenem, has increasingly been reported. This study was conducted to determine the prevalence of NDM-1 beta-lactamases in klebsiella pneumonia isolates through PCR method. Materials and methods: In this descriptive-analytic study, 120 klebsiella pneumonia isolates collected from patients with Lung infection and UTI were subjected to bacteriological tests. The samples were cultured and identified according to standard methods. Then, frequency of the strains producing extended spectrum beta-lactamases was determined with Disk diffusion method. Using kite method, DNA was extracted and examined for the existence of NDM-1 gene by PCR. Result: out of the 120 klebsiella pneumonia isolates, 13 (10.83 %) isolates were ESBL positive, 7.5 % of which were positive for NDM-1 B-lactamases resistance gene. Conclusion: considering the increasing rate of the ESBLs producing strains, using the appropriate treatment protocol based on the antibiogram pattern of the strains is highly recommended.